BACTERICIDAL ACTIVITY OF RASA SINDOORA - *Gajanand Modi; Anurag Haritwal; Tribhuvan nath Mirsha (International Journal of Ayurveda and Pharma Research, 2019)
Infectious diseases are the health disorders that are caused by infection causing organisms which use human body for surviving, reproducing and colonizing. These organisms are known as pathogens. Gradually increasing microbial resistance has made it more complicated. Therefore, everyone wants to explore remedies from natural source. Rasa sindoora is a Kupipakva Rasayana which is very popular and is widely used in therapeutics. In vitro evaluation of its bactericidal activity against the strains of some bacteria those are responsible for disease was carried out in microbiology laboratory, SBLD Ayurved Vishwabharti. Agar well diffusion method and disc diffusion methods was followed to assess the bactericidal activity like bacteria Salmonella Sp., Staphylococcus aureus subsp. aureus, Pseudomonas aeruginosa, and Escherichia coli and the zone of inhibition were calculated. Staphylococcus aureus subsp.aureus and Escherichia coli show maximum zone of inhibition result. All the bacteria were found susceptible against samples of Rasa sindoora with different concentration. When Rasa sindoora concentration will be increasing the gradually microbial concentration will be decreasing. After calculation of minimum inhibitory concentration E.Coli Show Maximum susceptibility against Rasa sindoora on concentration of 0.50 mg/ml and Pseudomonas aeruginosa show minimum inhabitation against Rasa sindoora on concentration of 0.50 mg/ml.